2012
DOI: 10.1371/journal.pone.0036102
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Thermodynamic Dissection of Human Copper Transfer from Chaperone to Target Protein

Abstract: Transient protein-protein and protein-ligand interactions are fundamental components of biological activity. To understand biological activity, not only the structures of the involved proteins are important but also the energetics of the individual steps of a reaction. Here we use in vitro biophysical methods to deduce thermodynamic parameters of copper (Cu) transfer from the human copper chaperone Atox1 to the fourth metal-binding domain of the Wilson disease protein (WD4). Atox1 and WD4 have the same fold (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(62 citation statements)
references
References 36 publications
2
59
1
Order By: Relevance
“…Cu transfer from Atox1 to metal-binding domains of the Wilson disease and Menkes disease proteins proceeds via (stable or transient) copper-bridged hetero-dimer complexes where the metal is shared between the two proteins' metal-binding site cysteines in tri-coordinate arrangements (Banci et al 2005;Achila et al 2006;Banci et al 2008Banci et al , 2009). In agreement with NMR data (Banci et al 2009), we showed earlier that upon mixing of Cu-Atox1 and the fourth metal-binding domain of Wilson disease protein (WD4), a stable ternary complex is formed in equilibrium with both substrates and products (Niemiec et al 2012), whereas mixing of CuAtox1 with a two-domain construct of metal-binding domains 5 and 6 of the Wilson disease protein (WD56) resulted in Cu transfer but no detectable heterocomplex (Nilsson et al 2013).…”
supporting
confidence: 84%
See 4 more Smart Citations
“…Cu transfer from Atox1 to metal-binding domains of the Wilson disease and Menkes disease proteins proceeds via (stable or transient) copper-bridged hetero-dimer complexes where the metal is shared between the two proteins' metal-binding site cysteines in tri-coordinate arrangements (Banci et al 2005;Achila et al 2006;Banci et al 2008Banci et al , 2009). In agreement with NMR data (Banci et al 2009), we showed earlier that upon mixing of Cu-Atox1 and the fourth metal-binding domain of Wilson disease protein (WD4), a stable ternary complex is formed in equilibrium with both substrates and products (Niemiec et al 2012), whereas mixing of CuAtox1 with a two-domain construct of metal-binding domains 5 and 6 of the Wilson disease protein (WD56) resulted in Cu transfer but no detectable heterocomplex (Nilsson et al 2013).…”
supporting
confidence: 84%
“…We found that Cu binding to CCS 1 , like to Atox1 (Niemiec et al 2012), can be probed via changes in the 254 nm/280 nm absorbance ratio since Cu binding to the thiols in the Cys side chains results in increased 254 nm absorbance while the 280 nm absorbance remains constant. Cu titrations to CCS 1 -probed by 254/280 nm absorption ratio of the CCS 1 peak after gel filtration separation (to remove reducing agent that may affect the absorption)-show that Cu binds stoichiometrically forming a 1-to-1 complex with CCS 1 at these conditions (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations